Transformation of T-Cell Acute Lymphoblastic Lymphoma to Peripheral T-Cell Lymphoma: A Report of Two Cases - Michael Markow; Abu-Sayeef Mirza; Lia Perez; Haipeng Shao; Pedro Horna; Claudio Anasetti; Lubomir Sokol; Mohammad O. Hussaini (Case Reports in Hematology)
Nonhepatosplenic/noncutaneous γδ peripheral T-cell lymphoma (NHNCγδ PTCL) represents a miscellaneous group of unrelated T-cell lymphomas of which only isolated cases have been reported. We describe two cases of transformation from T-lymphoblastic leukemia/lymphoma to NHNCγδ PTCL. Transformation into more aggressive disease is a rare event in T-cell lineage-derived hematologic malignancies compared to B-cell neoplasms. Nevertheless, both of our cases involved relapse as PTCL manifested with skin involvement and an overt shift from blastic morphology to large granular leukemia-like mature T cells. Among other notable molecular characteristics, expression of immature markers such as TdT was lost in both cases. Based on cytogenetics, phenotype, and morphology, both patients represent a novel phenomenon of clonal transformation from T-ALL to PTCL which has rarely been reported in the literature. Such transformation may carry important diagnostic and biological implications.